Unveiling the Aggregated Effect of Entrepreneurial Orientation on Enterprise Performance - Chakrabarti, Deepankar; Das, Subhasish; Shrivastava, Amit; Mohanty, Debasis; Matta, Rahul (Prabandhan: Indian Journal of Management, 2025)
Purpose : The current research examined the combined effect of entrepreneurial orientation (EO) on enterprise performance (EP) and sought to present a comprehensive perspective of how EO influenced EP. Methodology : Drawing on 42 studies with a total sample size of 9,523, this research assessed heterogeneity, detected publication bias using the “Trim & Fill method,” and calculated the overall effect size between EO and EP. Findings : The analysis revealed a positive correlation between EO and EP, with an aggregated effect size of 0.63 (95% confidence interval: 0.61–0.65) and a PI of (–0.20 to 1.46). However, heterogeneity was extremely high at I² = 97.37%, indicating considerable variability among studies. Egger’s regression and the Begg & Mazumdar test were conducted to evaluate whether publication bias contributed to this heterogeneity. Both tests revealed no substantial evidence of publication bias, confirming the reliability of the findings despite the observed heterogeneity. Practical Implications : Enterprises with higher EO, characterized by a penchant for innovation, initiative, and risk-taking, are generally more likely to perform better. A sensible approach may involve adapting EO attributes to the specific market environment and organizational resources. Additionally, businesses must balance the dimensions of EO to ensure that plans are tailored to the firm’s unique competitive landscape, thus avoiding excessive risk and resource allocation. Originality/Value : The study offered a valuable benchmark for future research, enabling its use as a mean effect size when testing the null hypothesis. In the future, the sectoral dynamics of EO and EP should be explored, recognizing that core principles and effectiveness varied significantly across industries.